Luther. Season 4 [videorecording (DVD)] - Elba, Idris; Leslie, Rose, 1987-; Malahide, Patrick (BBC Home Entertainment, 2015)
Pitted against his most chilling adversary yet, Luther is haunted by past ghosts and hellbent on revenge as the Serious Crime Unit faces its most challenging psychological duel to date. There is no question he will come close to the edge, but will he finally go over?